Masters of Dissent: Leonardo Sciascia and the Lesson of Polish Writers - Schembari, Andrea (Poznańskie Studia Polonistyczne. Seria Literacka, 2020)
The article focuses on the intertextual presence of Polish writers in Leonardo Sciascia’s work. Highlighted in this context is the possible influence on the Sicilian writer of the peculiar expression of “dissent” by writers such as Sienkiewicz, Brandys and Lec. The article closes with a brief comparison between the protagonists of Il cavaliere e la morte by Sciascia and Odpocznij po biegu (Rest after run) by Terlecki, both restless investigators disobedient to the authorities.